Keragaan Karakter Agronomi Beberapa Galur Tanaman Padi (Oryza sativa L.) - Gonda, Gregorius; Andayani, Neny; Parwati, Wiwin Dyah Ully; Widyayani, Setyorini (Program Studi Agroteknologi INSTIPER, 2025)
Efforts to increase rice production are being made thru plant breeding activities, including testing or evaluating the agronomic characteristics of promising lines. The purpose of this study is to evaluate the agronomic characteristics of several promising rice lines, namely lines GKYGK 1, GKYGK 2, GKYGK 3, and GKYGK 4, compared to the Gilirang and Segreng Handayani varieties. The research was conducted from November 2022 to March 2023 in Mojosari Village, Playen District, Gunungkidul Regency, Yogyakarta. The tested rice lines and their control varieties were planted in plots measuring 500 m2 each, using the legowo planting system with a spacing of 2:1 or (25 X 12.5 X 50) cm. From each line, 4 tillers were sampled to observe several agronomic characteristics including: plant height, number of productive tillers, panicle length, flag leaf length, flag leaf width, grain length, grain width, number of filled grains, number of empty grains, grain weight per tiller, and weight of 1,000 grains. In addition, yield from the harvested area was also observed. The data obtained were then analyzed using Analysis of Variance (ANOVA). If there were significant differences, the testing was continued with Duncan's New Multiple Range Test (DMRT) at the 5% level. The research results showed that the GKYGK 3 line had high yield potential in several characteristics, such as having the shortest plant height (117.31 cm), the highest 1,000-grain weight of filled grains (29.43 g), and the highest yield per square meter (9.688 kg). The GKYGK 1 line had high yield potential, such as having the highest number of productive tillers (18.56 stems), the longest panicle length (28.47 cm), and the highest grain weight per clump (60.68 g). The GKYGK 2 line had the highest percentage of filled grains (79.33%) and the longest grain length (10.53 mm).